Izin Kegiatan Usaha Perdagangan Bagi Usaha Online - Erida Putri Yulianita (2019)
This study examines licenses for trading business activities for online business which to date have not been specifically regulated in statutory regulations. The type of research used in this thesis is doctrinal research. The approach method used is statute approach to study exiting legal problems. The legal material from this research comes from books, journals, newspapers, and the internet related to licensing and trade law. Through this research the author discusses the concept of trading business license for online business that can be equated with conventional business actors in order to create equal treatment for online business and conventional business. This research refers to the relevant laws and regulations to produce an understanding of deepening of trading business license for online business, both in terms of benefit and assessment.